Sistem Pakar Diagnosa Gangguan Pencernaan Pada Manusia Menggunakan Metode Certainty Factor - Desi Endiyana Br.Purba; R. Mahdalena Simanjorang (Jurnal Sains dan Teknologi, 2022)
Along with advances in science and technology, especially in the field of medicine, more sophisticated medical equipment will be produced in fighting disease or making early detection of disease so that treatment can be faster. One of them is digestive disorders in humans. The purpose of this study is to build an expert system application that is able to diagnose digestive disorders in humans based on the symptoms experienced by implementing the Certainty Factor method. The development of an expert system uses the waterfall model, which consists of the stages of analysis, formulating problems, collecting data, and testing. The implementation of the Certainty Factor method in this expert system is used to generate a level of confidence in the diagnosis of the disease. The expert system was tested through 3 stages of testing, namely blackbox test, validity test and user test. In the blackbox test, the system functions run as expected. In the validity test, the system is declared valid for use. In the user test, respondents gave the criteria of "Eligible". From the results of the study, it can be concluded that the system is able to provide a trust value and can diagnose digestive disorders based on the symptoms entered by the user. Because the system is still limited, it is hoped that there will be system development with other methods so that it is more useful for users